Analisis Kampanye Sosial Gempur Rokok Ilegal Bea Cukai Periode Tahun 2022 – 2023 - Supriadi, Idris; Hamad, Ibnu; Sari, Yunita (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
This research analyzes the strategic communication design and implementation of the "Gempur Rokok Ilegal" campaign conducted by the Directorate General of Customs and Excise during 2022–2023, as well as evaluating public awareness levels toward the campaign. The study employed a concurrent mixed methods approach with a constructivist paradigm, integrating the SOSTAC model and McQuail Windahl’s communication framework for qualitative analysis through case studies and in-depth interviews with campaign officials, while the quantitative analysis utilized an online survey of 1,000 validated respondents. Findings reveal the campaign demonstrates a strategic evolution from passive communication to participatory communication that integrates repressive and persuasive approaches. Multi-platform implementation with a dominance of social media achieved high effectiveness scores across three dimensions: affective (4.58), conative (4.55), and cognitive (4.53) on a 5.0 scale, indicating success in building emotional awareness, positive behavioral intentions, and factual understanding regarding illegal cigarettes. Instagram and TikTok effectively reached 66.1% of respondents with optimal exposure frequency, while content integration through news media and institutional accounts created dual credibility that strengthened message legitimacy.